1995
DOI: 10.1002/1520-6629(199504)23:2<167::aid-jcop2290230207>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Cultural conflicts and problem behaviors of Latino adolescents in home and school environments

Abstract: This empirical study examines the behavioral sequelae of acculturation strains among Latino adolescents in home ans school settings. Two theoretically derived hypotheses are tested. First, low acculturation Latinos experiencing strains associated wsith rapid cultural and language transitions will have more behavior problems reported by their parents and teachers. Second, highly acculturated Latinos reporting more acculturation strains. associated with perceptions of prejudical treatment and internalization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
141
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(156 citation statements)
references
References 17 publications
11
141
4
Order By: Relevance
“…Studies have found that Chinese American adolescents report being discriminated against by teachers or other adults at schools (Qin, Way, & Rana, 2008 ), and racial discrimination is positively associated with behavior problems among Latino American adolescents (Vega, Khoury, Zimmerman, & Gil, 1995 ). Importantly, immigrant children from different ethnic backgrounds may have varying types of racial discrimination experiences.…”
Section: Racial D Iscrimination and P Rejudicesupporting
confidence: 93%
“…Studies have found that Chinese American adolescents report being discriminated against by teachers or other adults at schools (Qin, Way, & Rana, 2008 ), and racial discrimination is positively associated with behavior problems among Latino American adolescents (Vega, Khoury, Zimmerman, & Gil, 1995 ). Importantly, immigrant children from different ethnic backgrounds may have varying types of racial discrimination experiences.…”
Section: Racial D Iscrimination and P Rejudicesupporting
confidence: 93%
“…However, it should be noted that the ARSMA-II focuses primarily on behavioral indicators of cultural orientation, such as language use and ethnic affiliation. Like most scales used in prior research on acculturation (e.g., Marin & Gamba, 1996), the ARSMA-II does not measure underlying values associated with these behavioral indicators, despite the fact that many theorists maintain that traditional value shifts may better account for psychological functioning and risk behavior for Latinos (Marin, 1992;Vega, Khoury, Zimmerman, Gil, & Warheit, 1995).…”
Section: Dual Processes Of Acculturation and Enculturationmentioning
confidence: 99%
“…In their work with Cuban Americans, for example, Szapocznik and Kurtines (1993) proposed that discrepancies between parents and youth in acculturation contribute to problematic parent -adolescent relationships and youth maladjustment. Other researchers have highlighted the potential negative implications of intergenerational discrepancies for parent -child relationships in immigrant families (Phinney, Ong, & Madden, 2000;Rumbaut, 2005;Vega, Khoury, Zimmerman, Gil, & Warheit, 1995).…”
Section: Parents' Cultural Orientations and Adolescents' Peer Involvementioning
confidence: 99%
“…In their work with Cuban Americans, for example, Szapocznik and Kurtines (1993) proposed that discrepancies between parents and youth in acculturation contribute to problematic parent -adolescent relationships and youth maladjustment. Other researchers have highlighted the potential negative implications of intergenerational discrepancies for parent -child relationships in immigrant families (Phinney, Ong, & Madden, 2000;Rumbaut, 2005;Vega, Khoury, Zimmerman, Gil, & Warheit, 1995).Building on these ideas, we hypothesized that incongruence between parents' cultural orientations and adolescents' peer time would be associated with more problematic adjustment and less parental acceptance. Specifically, we examined two types of mismatches between parents' cultural orientations and adolescents' time spent with peers: parents' Mexican orientations and adolescents' time with non-Mexican peers and parents' Anglo orientations and adolescents' time with Mexican peers.…”
mentioning
confidence: 99%